Colonisation pattern of nonpathogenic Fusarium oxysporum, a potential biological control agent, in roots and rhizomes of tissue cultured Musa plantlets - Paparu, P.; Dubois, T.; Gold, C.; Niere, B.; Adipala, E.; Coyne, Danny L. (Wiley, 2006)
Under laboratory conditions, nonpathogenic, endophytic Fusarium oxysporum inflicts high mortality among banana weevils and nematodes. Following inoculation into banana (Musa spp.) tissue cultured plants, successful colonisation is necessary for efficient biological control of these pests. The pattern of root and rhizome colonisation by two nonpathogenic Ugandan F. oxysporum strains (V2w2 and III4w1) in cv. Nabusa (AAA-EA) was investigated using light microscopy. Percentage of colonisation in the rhizomes (93%) was higher than in the roots (56%), but hyphal density in the roots (0.30 mm−2) was higher than in the rhizomes (0.21 mm−2). The root bases were better colonised (76%) than root midsections (53%) or tips (39%). Both the strains colonised the roots and the rhizomes, with numerous hyphae infecting the hypodermis but fewer infecting the cortex. Colonisation of vascular tissues was not recorded. Despite the presence of hyphae in intercellular and intracellular spaces of the roots and the rhizomes, normal cell structure was observed. Our report provides the first in situ observation and quantification of endophyte colonisation in banana. The study demonstrated the ability of F. oxysporum strains V2w2 and III4w1 to penetrate intact host tissues and recolonise the host internally upon inoculation, an important step for their suitability as biological control agents.